Spatial and Temporal Variations of a Screening Current Induced Magnetic Field in a Double-Pancake HTS Insert of an LTS/HTS NMR Magnet - Ahn, Min Cheol (2009)
This paper presents experimental and simulation results of a screening current induced magnetic field (SCF) in a high temperature superconductor (HTS) insert that constitutes a low-/high-temperature superconductor (LTS/HTS) NMR magnet. In this experiment, the HTS insert, a stack of 50 double-pancake coils, each wound with Bi2223 tape, was operated at 77 K. A screening current was induced in the HTS insert by three magnetic field sources: 1) a self field from the HTS insert; 2) an external field from a 5-T background magnet; and 3) combinations of 1) and 2). For each field excitation, which induced an SCF, its axial field distribution and temporal variations were measured and compared with simulation results based on the critical state model. Agreement on field profile between experiment and simulation is satisfactory but more work is needed to make the simulation useful for designing shim coils that will cancel the SCF.